Images of Kabīr - Horstmann, Monika (South Asian studies, 2002)
Contributed articles on life and works of Kabir, 15th century Hindi devotional poet, presented at an international symposium commemorating the six-hundred anniversary of Kabir held at Heidelberg in 1999
Mit Reg
Includes index - Includes bibliographical references - Includes verses in Avadhi - (Devanagari and roman)
Keywords: Kabir -- 15th cent -- Criticism and interpretation -- Congresses; Konferenzschrift; Konferenzschrift -- 1999 -- Heidelberg; Kongress; Kabir